Case Report: Pediatric Hepatic Rhabdomyosarcoma With Maximum Lifetime - Li, Xu; Li, Xiang; Yang, Dian-Fei; Li, Miao; Xu, Hong-Qin; Zheng, Shuang; Gao, Pu-Jun (Frontiers in Medicine, 2022)
Primary intrahepatic rhabdomyosarcoma is an extremely rare malignant tumor. Here, we describe a case of embryonal rhabdomyosarcoma of the liver in a 7-year-old boy without any symptoms. Serologically, the patient showed abnormal levels of serum tumor markers and liver function. Imaging revealed a large mass in the left lobe of the liver and no lesions elsewhere. At first, the patient was misdiagnosed by percutaneous liver biopsy as having clear cell sarcoma. However, the final diagnosis was established to be hepatic embryonal rhabdomyosarcoma based on postoperative histopathology and typical immunohistochemical staining, which was positive for desmin and myogenin. For treatment, the patient received two cycles of preoperative chemotherapy, prophylactic radiotherapy, and 13 cycles of combined postoperative chemotherapy. Routine follow-ups after all treatment conducted by imaging examinations showed no sign of recurrence or metastasis over 13 months, and the patient survives more than 38 months since initial diagnosis. To our knowledge, this patient is the first with hepatic rhabdomyosarcoma to receive neoadjuvant chemotherapy (preoperative chemotherapy) combined with relative comprehensive treatment and achieve a favorable result.